2013
DOI: 10.4103/1319-2442.121288
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of glomerular disease in the Saudi population: A single-center, five-year retrospective study

Abstract: Glomerular diseases continue to be the leading cause of end-stage renal disease (ESRD) globally. Hence, it is important to recognize the pattern of glomerular diseases in different geographical areas in order to understand the patho-biology, incidence and progression of the disorder. Published studies from different centers in Saudi Arabia have reported contradicting results. In this retrospective study, we report our experience at the Armed Forces Hospital, Riyadh, Saudi Arabia. A total of 348 native renal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“… 12 Likewise, most studies in the Kingdom have reported LN as the most common cause of secondary GN. 6 The 38.6% prevalence of LN in our entire cohort was much higher than that reported in other series. In the largest study from the Kingdom, reported in 2000, SLE was associated with 126 GN cases; 17.7% of the cohort comprised primary and LN cases.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“… 12 Likewise, most studies in the Kingdom have reported LN as the most common cause of secondary GN. 6 The 38.6% prevalence of LN in our entire cohort was much higher than that reported in other series. In the largest study from the Kingdom, reported in 2000, SLE was associated with 126 GN cases; 17.7% of the cohort comprised primary and LN cases.…”
Section: Discussioncontrasting
confidence: 64%
“…Focal segmental glomerulosclerosis is typically reported as the most common primary GN; however, MCD, MGN, and MPGN have also been reported to have the highest prevalence, although longitudinal data from similar catchment areas are not available. 6 Registry data were published in 2000 from 4 hospitals in Riyadh, one in Jeddah, and one in the eastern province, which included 782 adult patients with GN. 3 Similar to our patients, FSGS was also the predominate pattern, observed in 21.3% of adult biopsies with primary GN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 7 ] In contrast, its prevalence in Bangladesh and Saudi Arabia is low, at 7.37% and 9.90%, respectively. [ 8 , 9 ] IMN has been also reported to have a greater prevalence in Caucasians than in Asians. [ 10 ] IMN accounts for 20% to 30% of nephrotic syndrome cases in Caucasian adults, and this proportion is also increasing in Asian adults.…”
Section: Introductionmentioning
confidence: 99%
“…A single-center study performed by Pan et al [4] found that the prevalence of MN has kept increasing during the past decades from 6.48% in 1997-1999 to 22.79% in 2009-2011. However, MN is less common in Bangladesh and Saudi Arabia, accounting for 7.37 and 9.90% of PGN patients, respectively [5,6]. In addition, idiopathic MN (IMN) accounted for 12.3 and 12.0% of all renal biopsies in Korea and Oman, respectively [7,8].…”
Section: Introductionmentioning
confidence: 99%